2010
DOI: 10.1108/03074351011039445
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear interest rate exposure in Spain

Abstract: PurposeThis paper aims to carry out a comprehensive analysis of the influence of interest rate risk on Spanish firms at the industry level.Design/methodology/approachThe methodology employed has its origin in the two‐index linear regression model proposed by Stone. This traditional interest rate exposure model has been extended in this paper to allow for a nonlinear exposure component as well as the presence of asymmetric behaviour in the exposure pattern.FindingsInterest rate exposure is not homogeneous for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…This implies that, in general, the linear interest rate exposure of Spanish banks is economically more important than the nonlinear exposure measured using a cubic function. This finding coincides with that reported by Ferrer et al (2010) for the banking sector in an analysis of the interest rate exposure of Spanish firms carried out at the industry level.…”
Section: Nonlinear Interest Rate Exposuresupporting
confidence: 91%
See 1 more Smart Citation
“…This implies that, in general, the linear interest rate exposure of Spanish banks is economically more important than the nonlinear exposure measured using a cubic function. This finding coincides with that reported by Ferrer et al (2010) for the banking sector in an analysis of the interest rate exposure of Spanish firms carried out at the industry level.…”
Section: Nonlinear Interest Rate Exposuresupporting
confidence: 91%
“…In the same vein, Hallerbach (1994) Following a usual practice in the literature (Flannery and James, 1984;Hirtle, 1997;Benink and Wolff, 2000;Soto et al, 2005;Ferrer et al, 2010), weekly stock returns, adjusted for dividends and stock splits, are employed. The weekly returns are calculated from Wednesday to Wednesday using closing stock prices in order to prevent the possible bias associated to the weekend effect.…”
mentioning
confidence: 99%
“…Ferrer et al . () and Park and Choi () examined the interest rate exposure of Spanish industry portfolios and US property/liability insurer stock returns respectively. Although they found that more industries were significantly exposed to the long‐term interest rate than the short‐term interest rate, however the exposure coefficients were negative for both interest rate measures.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The findings indicated that exposure to changes in the long-term interest rates was mostly positive and firms exhibited higher exposure towards the long-term interest rate than the shortterm interest rate. Ferrer et al (2010) and Park and Choi (2011) examined the interest rate exposure of Spanish industry portfolios and US property/ liability insurer stock returns respectively. Although they found that more industries were significantly exposed to the long-term interest rate than the short-term interest rate, however the exposure coefficients were negative for both interest rate measures.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…In empirical economics, polynomial specifications can be found in many subfields, such as, financial economics [15,16], labor economics [17,18], agricultural economics [19], macroeconomics (exchange rates, [20]) and environmental economics [21,22]. An evocative example can be found in the empirical research dealing with the Kuznets curve and the environmental Kuznets curve; the inverse U-shaped relationship between the variables is typically specified as the dependent variable regressed on the independent and its square (see [23,24]; it is noteworthy that Kuznets' specifications usually employ even-order polynomials).…”
Section: Introductionmentioning
confidence: 99%